The Online Research of B2O3 on Crystal Behavior of High Ti-Bearing Blast Furnace Slag - Yin-he Lin; Bin Zheng; Lin-gen Luo; Yu-long Jia; Li-qiang Zhang (Journal of Chemistry)
The existence and phase structures of high Ti-bearing blast furnace slag at a high temperature are the key issue to flow performance and reaction temperature. It is essential to evaluate the physical-chemical properties, such as viscosity and melting point In this work, a new method of online research of B2O3 on crystal behavior of high Ti-bearing blast furnace slag is proposed. By ultrahigh-temperature confocal laser scanning microscope and area scanning analysis, it can be concluded that the effect of B2O3 additives on the viscosity has a more obvious effect among the low-temperature region of the slag. Compared to the samples without B2O3 additives, the liquid phase of Ti-bearing slag with B2O3 additives appears earlier at the same experimental temperature, and the solid particles floating on the surface of liquid slag become less. Moreover, the B2O3 additives can promote the migration of titanium elements from the high melting point phase to the low melting point phase, and the transferring quantity increases with the addition of the amount of B2O3 additives. These results demonstrate that B2O3 additives can restrain the appearance of the perovskite phase, decrease the apparent viscosity, and promote the metallurgical properties of Ti-bearing blast furnace slag.